PROPORTIONALITIES OF JUDGE'S DECISIONS ON THE POSITION OF CONCURRENT CREDITORS AS AN EFFORT TO ENFORCEMENT OF LEGAL CERTAINTY OF THE PARTIES IN BANKRUPTCY DISPUTES - Satino, Satino; Fauzan, Muhammad (UNTAG Law Review, 2023)
Bankruptcy which is a condition in which the debtor is unable to make payments on his debts to creditors. In the dispute process, there is a sequence of creditor levels which will affect the settlement of creditor receivables, namely preferential, separatist and concurrent creditors. Concurrent creditors who are at the last level make their position very vulnerable to not getting their receivables repaid. This requires further research in this regard. This study uses a normative legal method which will analyze legal sources and legal literature related to the topics discussed. This research will discuss 1) what is the position of concurrent creditors in bankruptcy disputes and 2) how is the proportionality of the judge's decision on the position of concurrent creditors in bankruptcy disputes as an effort to enforce the legal certainty of the parties? The results of this study indicate that the position of concurrent creditors in bankruptcy disputes is that creditors are the most recent in paying off their receivables. Then the proportionality of the judge's decision on concurrent creditors is given to the supervisory judge as the party who has the authority to distribute the proceeds from the sale of the bankrupt debtor's assets. Concurrent creditors will receive results based on Article 189 Paragraph (3) Law Number 37 of 2004 concerning Bankruptcy and Postponement of Debt Suspension Obligations.